Quality of life of cervical cancer patients - Mayang Wulan; Yuzana Binti Mohd Yusop; Harmy Bin Mohamed Yusoff (Universitas Muhammadiyah Surabaya, 2020)
ABSTRACT Cervical cancer is known as the highest cause of death after breast cancer. It is gynecological cancer contributing to the top cause of death in women. Sexual and reproductive issues can reduce the quality of life of women with cervical cancer. WHO defines the quality of life as an individual's perception in the cultural context and value system in which the individual experiences and is related to their goals, expectations, standards, and affairs. It gives the concept of an individual's physical health, psychological conditions, one's beliefs, social relationships, and one's involvement with something meaningful in their environment. This article will explain the definition, symptoms, and staging of cervical cancer, the definition of the quality of life, the meaning of excellence for the cervical cancer patient, and the facts that affect the quality of life. Keywords : quality of life, cervical cancer, reproductive organ cancerCorrespondence : mayangwulan8@gmail.com